Effect of ionic liquids on the morphology and mesophase formation of electrospun polylactide nanofibers. (18th May 2015) - Na, Bing; Zhang, Peng; Lv, Ruihua; Tian, Renping; Ju, Yunhui; Liu, Qingxian
Abstract: Electrospinning of polylactide (PLA) solutions produces coarse nanofibers mixed with numerous beads at the adopted conditions. Incorporation of ionic liquids with high conductivity in the solutions, however, promotes formation of fine PLA nanofibers with diameters of about 70 nm. It corresponds to significant stretching of the solutions as well as remarkable molecular alignment under the electrical field. As a result, high amount of mesophase besides a few crystals is induced in the fine PLA nanofibers. It is responsible for the accelerated cold crystallization above glass transition temperature. Notably, an enhancement in the melting point of about 10 °C is exhibited by the crystals transformed from the mesophase with remarkable molecular alignment in the fine PLA nanofibers. Graphical abstract: Highlights: Ionic liquids promoted formation of fine PLA nanofibers by electrospinning. The fine PLA nanofibers had average diameters of about 70 nm. High amount of mesophase was induced in the fine PLA nanofibers. Mesophase accounted for accelerated cold crystallization and high melting point.